CHILD’S MUSICAL PERCEPTION DEVELOPMENT IN EARLY YEARS - Līduma, Anna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
This research is an analysis of the succession in the child’s musical perception development. The theory based experimental study of the gradual development of musical perception revealed the specifics of children’s musical perception formation from prenatal period to the age of 3. The formation of the sensory and vocal experience in early years, and purposeful activity at the realization of the connection of memory and thinking in conjunction with listening to music are analyzed. The author has observed that both stages of musical perception in the early genesis: sensory and motor and a perceptive activity; perceptive activity gets developed during purposeful musical everyday actions. On the basis of pedagogical observations and self-experience at preschool, the role of adult’s purposeful activity in the timely started promotion of the child’s musical perception is highlighted.